2019
DOI: 10.1002/art.40724
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Surrogate Kidney End Points for Lupus Nephritis Clinical Trials: Development and Validation of a Novel Approach to Predict Future Kidney Outcomes

Abstract: HITs, derived from short-term kidney responses to treatment correlate with long-term kidney outcomes, and now must be validated as surrogate endpoints for LN clinical trials. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 27 publications
2
27
0
1
Order By: Relevance
“…In terms of monitoring of LN, a number of posthoc analyses of major studies in LN suggested the value of an early proteinuria response, together with a normal serum creatinine, within 12 months, to predict a favourable long-term outcome of patients. 60 8285 By contrast, glomerular haematuria was consistently shown in the same studies to add no predictive value in these prognostic models. Although these findings may not necessarily impact routine clinical practice, where urine microscopy will continue to be part of patient monitoring, however, they may well carry implications regarding future design of optimal endpoints for clinical trials.…”
Section: Discussionmentioning
confidence: 93%
“…In terms of monitoring of LN, a number of posthoc analyses of major studies in LN suggested the value of an early proteinuria response, together with a normal serum creatinine, within 12 months, to predict a favourable long-term outcome of patients. 60 8285 By contrast, glomerular haematuria was consistently shown in the same studies to add no predictive value in these prognostic models. Although these findings may not necessarily impact routine clinical practice, where urine microscopy will continue to be part of patient monitoring, however, they may well carry implications regarding future design of optimal endpoints for clinical trials.…”
Section: Discussionmentioning
confidence: 93%
“…In monitoring renal response, reduction of UPr (to less than 0.8 g/day) following treatment is more important than residual haematuria 21. Patients with more severe proteinuria and longer-standing disease are less likely to respond or show more delayed responses 22 23…”
Section: Resultsmentioning
confidence: 99%
“…Post hoc analyses from the MAINTAIN and Euro-Lupus Nephritis Trials suggest that proteinuria at 12 months represents the best single predictor for long-term renal outcome (ie, risk for end-stage kidney disease (ESKD) or doubling of serum creatine after 10 years). [23][24][25][26][27] Accordingly, therapy should aim for proteinuria <0.5-0.7 g/24 hours by 12 months (complete clinical response), although up to 50% of patients not reaching this milestone may still have stable longterm kidney function. 25 28 Evidence of improvement in proteinuria (with GFR normalisation/stabilisation) should be noted by 3 months, 29 30 and at least 50% reduction in proteinuria (partial clinical response) by 6 months.…”
Section: Treatment Of Adult Ln Goals Of Treatmentmentioning
confidence: 99%